Ceramide-transfer protein-mediated ceramide transfer is a structurally tunable flow-inducing mechanism with structural feed-forward loops. Issue 6 (27th June 2018) - Giordano, Giulia
Abstract : This paper considers two models of ceramide-transfer protein (CERT)-mediated ceramide transfer at the trans -Golgi network proposed in the literature, short distance shuttle and neck swinging, and seeks structural (parameter-free) features of the two models, which rely exclusively on the peculiar interaction network and not on specific parameter values. In particular, it is shown that both models can be seen as flow-inducing systems, where the flows between pairs of species are tuned by the concentrations of other species, and suitable external inputs can structurally regulate ceramide transfer. In the short distance shuttle model, the amount of transferred ceramide is structurally tuned by active protein kinase D (PKD), both directly and indirectly, in a coherent feed-forward loop motif. In the neck-swinging model, the amount of transferred ceramide is structurally tuned by active PI4KIIIβ, while active PKD has an ambivalent effect, due to the presence of an incoherent feed-forward loop motif that directly inhibits ceramide transfer and indirectly promotes it; the structural role of active PKD is to favour CERT mobility in the cytosol. It is also shown that the influences among key variables often have structurally determined steady-state signs, which can help falsify the models against experimental traces.